Pengaruh Kualitas kehidupan kerja, Budaya Organisasi dan Keterikatan Karyawan Pada Trini Karya Yogyakarta - Nodi Pebriyansyah (Universitas Muhammadiyah Tangerang, 2021)
This study discusses how the influence of the quality of work life and organizational culture on employee engagement as a moderating variable. This study aims to determine the effect of the quality of work life and organizational culture on employee engagement as a moderating variable. This research uses primary data obtained by distributing questionnaires to employees who work at Trini Karya Yogyakarta, totaling 30 respondents with saturated sampling technique. Data analysis in this study is quantitative data analysis. This analysis includes the reliability test, validity test, statistical test through the Ttest, Ftest test, and the coefficient of determination R2, the classical assumption test and the Moderation Test.The research results show that after going through the above test, it is known that the quality of work life has a significant effect on employee performance as indicated by a significant value of 0.001 (0.001 (0.001 <0.05), this value can prove the hypothesis is accepted. Organizational culture does not have a significant effect. indicated by a significant value of 0.122 (0.122> 0.05), this value can prove the hypothesis is rejected.Employee engagement has no significant effect on employee performance as indicated by a significant value of -0.149 (0.0149> 0.05), this value prove the hypothesis is rejected. Keywords : Quality Of Work, Organizational Culture, , Employee Engagement, Employee Performance